Minding the Gap – of Indifference: Approaching ‘Performance Philosophy’ with Salomo Friedlaender (1871-1946) - Alice Lagaay (Performance Philosophy, 2015)
The concept of "Creative Indifference" put forward by Salomo Friedlaender in his 1918 magnum opus, Schöpferische Indifferenz, provides much food for thought from a Performance Philosophy perspective. Friedlaender's work, which has been largely overlooked by academic philosophers until now, was in fact hugely influential in expressionist Dada circles at the time of its publication. It also contributed to shaping Gestalt Therapy theories and practice, thereby relating to a number of bodywork movements that continue to inform performance practice and Performance Philosophy alike. In this short text, Alice Lagaay begins to explore the manner in which Friedlaender/Mynona can be seen as a Performance Philosopher “avant la lettre”, and how the notion of "Creative Indifference” might be fruitful in the ongoing "Mind-the-Gap”- debate relating to the relation between “Performance" and "Philosophy".